2001
DOI: 10.1007/bf03017358
|View full text |Cite
|
Sign up to set email alerts
|

Reproductibilité et interchangeabilité du Thromboélastographe®, Sonoclot® et du temps de coagulation activé (Hémochron®), en chirurgie cardiaque

Abstract: O Ob bj je ec ct ti if f : : Malgré une utilisation courante, la reproductibilité des mesures du Thromboélastographe® (TEG), du Sonoclot® (SCT), et de l Hémochron® mesurant le temps de coagulation activé avec célite ou kaolin (ACT-C et ACT-K), a été peu étudiée dans les conditions réelles d utilisation. La présente étude évalue la reproductibilité de ces mesures, et la possibilité de substituer l ACT-C par un des autres tests. Methods: Blood samples collected from 20 volunteers and 21 patients undergoing myoca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0

Year Published

2004
2004
2017
2017

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 23 publications
(6 citation statements)
references
References 26 publications
1
5
0
Order By: Relevance
“…Sonoclot analyzer has even demonstrated a precision close to that of thrombelastography. 26 In the present study we were able to show reliable results with reproducibility comparable with that of turbidimetric platelet aggregometry. One possible explanation for this better performance might be the different tests used in our study (GB and hepGB) compared with those used in earlier publications (predominantly testing of celiteactivated blood samples).…”
Section: Evolving Technology Tucci Et Alsupporting
confidence: 75%
“…Sonoclot analyzer has even demonstrated a precision close to that of thrombelastography. 26 In the present study we were able to show reliable results with reproducibility comparable with that of turbidimetric platelet aggregometry. One possible explanation for this better performance might be the different tests used in our study (GB and hepGB) compared with those used in earlier publications (predominantly testing of celiteactivated blood samples).…”
Section: Evolving Technology Tucci Et Alsupporting
confidence: 75%
“…Additionally, studies showed poor reproducibility of some of the measured parameters, especially CR and PF (22,23). However, others found the Sonoclot® Analyzer to be valuable and reliable in patients undergoing cardiac surgical procedures (24,25) and the Sonoclot® Analyzer has even demonstrated a precision close to that of thrombelastography (26). In more recent studies, test variability of ACT values determined by Sonoclot® were comparable to other established ACT analyzers (8-9% on average) (15)(16)(17)(18).…”
Section: Sonoclot Analysismentioning
confidence: 89%
“…Four studies were excluded because of insufficient data to judge the study design. [149][150][151][152] In the trial by Agarwal et al,…”
Section: Excluded Studiesmentioning
confidence: 99%